(untitled) (Fiep Bulletin - online, 2010)
The fights included in the school are usually adopted just as extracurricular activities, restricting their practice to only those who had some previous contact to justify its search as an extracurricular activity. This often stems from the fact the school did not see their educational potential and primarily from physical education teachers do not feel able to teach this activity during class. The aim of this study was to analyze the pedagogical possibilities that the contents of fights at school and may have help in training of students in a secondary school. A descriptive methodology was conducted by reviewing literature from respected authors in the field of physical education and related to the theme of fighting and physical education, seeking a theoretical and framing the questions on this theme. Through a brief historical review, it was possible to identify the model of contemporary physical education, which takes as its basic guiding principle and the body culture movement. More than a simple choice, the fight proved be valuable tool at all grade levels, especially in a secondary school. It is very important reflection the practice of the fights, or provide a breakdown of the paradigm of robotic movements and to guide to the principles of body culture of the movement.